2018
DOI: 10.1093/cercor/bhy109
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Adult Human Brain: Evidence from 5216 UK Biobank Participants

Abstract: Sex differences in the human brain are of interest for many reasons: for example, there are sex differences in the observed prevalence of psychiatric disorders and in some psychological traits that brain differences might help to explain. We report the largest single-sample study of structural and functional sex differences in the human brain (2750 female, 2466 male participants; mean age 61.7 years, range 44–77 years). Males had higher raw volumes, raw surface areas, and white matter fractional anisotropy; fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

108
558
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(678 citation statements)
references
References 121 publications
(154 reference statements)
108
558
10
2
Order By: Relevance
“…Men had larger global brain volume and surface area than women (IC1), which is consistent with previous studies (e.g., Ritchie et al, 2018). Additionally, women had higher subject weights in IC13, reflecting lower FA in the corticospinal tract, portions of the superior longitudinal fasciculi and posterior thalamic radiation compared to men, generally in line with a large-scale UK Biobank study (Ritchie et al, 2018). We also found that men had greater DMN amplitude (IC5) than women, which adds to previous inconclusive findings (Mowinckel et al, 2012;Weissman-Fogel, Moayedi, Taylor, Pope, & Davis, 2010) and contrasts a previous report suggesting effects in the opposite direction (Jamadar et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Men had larger global brain volume and surface area than women (IC1), which is consistent with previous studies (e.g., Ritchie et al, 2018). Additionally, women had higher subject weights in IC13, reflecting lower FA in the corticospinal tract, portions of the superior longitudinal fasciculi and posterior thalamic radiation compared to men, generally in line with a large-scale UK Biobank study (Ritchie et al, 2018). We also found that men had greater DMN amplitude (IC5) than women, which adds to previous inconclusive findings (Mowinckel et al, 2012;Weissman-Fogel, Moayedi, Taylor, Pope, & Davis, 2010) and contrasts a previous report suggesting effects in the opposite direction (Jamadar et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Men had larger global brain volume and surface area than women (IC1), which is consistent with previous studies (e.g., Ritchie et al, ). Additionally, women had higher subject weights in IC13, reflecting lower FA in the corticospinal tract, portions of the superior longitudinal fasciculi and posterior thalamic radiation compared to men, generally in line with a large‐scale UK Biobank study (Ritchie et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…While sex differences are well established for measures of restingstate functional connectivity in TD individuals (Biswal et al, 2010;Ritchie et al, 2018), these differences are currently poorly understood in autism partly due to the limited number of autistic females participating in neuroimaging studies. The question arises whether the brain functional organization differs between autistic males and females after taking typical sex differences into account.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, raw (sub)volumes of the amygdala were larger in men than in women by up to 11%. The third study contained more than 5,000 subjects (Ritchie et al, 2018) and revealed that, although men had a larger amygdala than women, the effect was only small (d = 0.18, bilaterally). Depicted are the area-specific trajectories (i.e., after removing the variance associated with sex and TIV) for the amygdala as a whole (AMG), as well as the centromedian (CM), laterobasal (LB), and superficial (SF) subareas were applied, sex differences were only small and not significant.…”
Section: Lack Of Sex Effects and Of Age-by-sex Interactionsmentioning
confidence: 98%